Next-Generation Desalination Membranes Empowered by Novel Materials: Where Are We Now? - Wu, Siqi; Peng, Lu Elfa; Yang, Zhe; Sarkar, Pulak; Barboiu, Mihail; Tang, Chuyang Y.; Fane, Anthony G. (Nano-Micro Letters, 2024)
Membrane desalination is an economical and energy-efficient method to meet the current worldwide water scarcity. However, state-of-the-art reverse osmosis membranes are gradually being replaced by novel membrane materials as a result of ongoing technological advancements. These novel materials possess intrinsic pore structures or can be assembled to form lamellar membrane channels for selective transport of water or solutes (e.g., NaCl). Still, in real applications, the results fall below the theoretical predictions, and a few properties, including large-scale fabrication, mechanical strength, and chemical stability, also have an impact on the overall effectiveness of those materials. In view of this, we develop a new evaluation framework in the form of radar charts with five dimensions (i.e., water permeance, water/NaCl selectivity, membrane cost, scale of development, and stability) to assess the advantages, disadvantages, and potential of state-of-the-art and newly developed desalination membranes. In this framework, the reported thin film nanocomposite membranes and membranes developed from novel materials were compared with the state-of-the-art thin film composite membranes. This review will demonstrate the current advancements in novel membrane materials and bridge the gap between different desalination membranes. In this review, we also point out the prospects and challenges of next-generation membranes for desalination applications. We believe that this comprehensive framework may be used as a future reference for designing next-generation desalination membranes and will encourage further research and development in the field of membrane technology, leading to new insights and advancements. Highlights: 1 The theoretical separation performance and practical separation performance of various membranes were collected and compared. 2 An up-to-date holistic and systematic evaluation of membranes from five dimensions (i.e., water permeance, water/NaCl selectivity, membrane cost, scale of development, and stability) is provided and visualized by radar charts. 3 The critical deficiencies revealed in the review are important in guiding the development of next-generation reverse osmosis membranes.